2007
DOI: 10.1111/j.1744-7976.2007.00089.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quality Characteristics on Consumers' Willingness to Pay for Gala Apples

Abstract: This paper uses individual apple-level data that include consumer sensory assessments and instrumental measurements of internal quality to analyze willingness to pay for Washington State Gala apples.Three distinct models are estimated: a model that includes destructive internal quality measures of apple characteristics, a model that utilizes only non-destructive internal quality measures, and a consumer model that includes subjective consumer sensory evaluations and consumer socio-demographic characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 17 publications
5
41
1
Order By: Relevance
“…Gala, with the exception of the period 1979-1990, has not been listed in the tables surveying the top ones. The main reason for this is probably its swift decrease of taste and other fruit characteristics during fruit storage of the cultivar (Volz et al 2003;McCluskey et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Gala, with the exception of the period 1979-1990, has not been listed in the tables surveying the top ones. The main reason for this is probably its swift decrease of taste and other fruit characteristics during fruit storage of the cultivar (Volz et al 2003;McCluskey et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Sensory description labels de Chernatony and Harris (2000) declared that providing an added value for the consumer might lead to higher prices and higher margins for the selling company. Furthermore, different products will have different sets of sensory characteristics, and the importance of the attributes that are present and communicated could also affect the consumers' willingness to pay (McCluskey et al, 2007). Fotopoulos and Krystallis (2003), who examined the Greek market and consumers' attitudes towards quality labels, found that consumers might be more willing to pay a higher or premium price for apples with a quality label.…”
Section: Sensory Descriptions When Comparing Food Productsmentioning
confidence: 99%
“…This result implies that consumers' orange juice acceptance may be strongly linked to what they experience when drinking the orange juice. Thus, if individuals have a good impression of an orange juice, they may repeat purchasing that orange juice (McCluskey et al, 2007). This also implies the importance of consumers' juice brand loyalty.…”
Section: Discussionmentioning
confidence: 99%
“…External attributes such as size, grade, cosmetic defects, and storage played a key role in price determination and product demand (Carew, 2000;Kim & House, 2012;Tronstad, Huthoefer, & Monke, 1992). On the other hand, eating-quality factors (internal food attributes) such as crispness, sweetness, acidity, and juiciness considerably influence whether consumers will repeat fruit purchases (McCluskey, Mittelhammer, Marin, & Wright, 2007).…”
Section: Introductionmentioning
confidence: 99%